Advances in Genesis of Soil-Water Salinity and Implications of GIS-XRD-EDXRF Explorations in Indus Plains of the Indian Sub-continent - Raj-Kumar (Journal of the Indian Society of Soil Science, 2026)
I am grateful to the Indian Society of Soil Science for giving me an opportunity to deliver the 13th Dr. N.P. Datta Memorial Lecture at G.B. Pant University of Agriculture and Technology which was organized by the local Chapter of the Indian Society of Soil Science.